Strategi Guru Dalam Mengatasi Kejenuhan Belajar Pada Pembelajaran SKI Materi Sunan Kudus di Kelas VI MI Pamokolan - delia delia; sri wahyuni; deuis suci rahmawati; maimunah (Jurnal Cahaya Edukasi, 2026)
This study aims to describe teacher strategies for overcoming learning boredom in Islamic Cultural History (ISCR) teaching Sunan Kudus as a subject in sixth-grade classes at Pamokolan Islamic Elementary School (MI Pamokolan). The study employed a qualitative approach with a descriptive approach. Subjects consisted of ISCR teachers and sixth-grade students at Pamokolan Islamic Elementary School. Data collection techniques included observation, interviews, and documentation. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing. The results indicate that student learning boredom is caused by the narrative nature of ISCR material, dominated by historical stories. To address this issue, teachers implemented a variety of learning strategies, combining lectures, storytelling, group discussions, question-and-answer sessions, and role-plays, supported by projectors. These strategies increased student participation, enthusiasm, and active participation during the learning process. Furthermore, the use of audio-visual media helped students understand abstract material in a more concrete and engaging way. Therefore, a varied, interactive, and media-supported learning strategy has proven effective in reducing student learning boredom in ISCR teaching Sunan Kudus as a subject in sixth-grade classes at Pamokolan Islamic Elementary School.